Designing Heritage Itineraries in Trainee Teachers Through Virtual Inter-University and Collaboration Groups: The Examples of Barcelona and La Laguna in Social Sciences Teaching - A. José Farrujia de la Rosa; Tània Martínez-Gil; Cristo Manuel Hernández Gómez; Isidora Sáez-Rosenkranz (Frontiers in Education, 2022)
In the following paper, we present some general results of an innovative teaching experience carried out by the University of La Laguna (ULL) and the University of Barcelona (UB). The project took place during a 6-week period by applying for cooperative work among early childhood (n = 109) and primary (n = 86) education trainee teachers in a selected virtual environment (ULL). One of the key aspects was the inter-university student’s grouping among both bachelor programs (early childhood and primary). The project had two main aims, which are as follows: (1) to familiarize students with heritage itineraries as key tools for the teaching of Social Sciences and (2) to develop professional competencies related to the coordination of teachers among educational levels, teaching, and learning strategies when using historical heritage and improving digital competencies. To achieve these aims, a three-phase intervention was designed (planning, design, and evaluation), all including active learning and the use of local environments as a teaching resource. To investigate the outcomes of the project, two sources of data were analyzed, namely, the results of a rubric and an opinion questionnaire (Cronbach’s α = 0.693), applied pre- (n = 185), and post- (n = 152) intervention. The descriptive statistical analysis was carried out with the Statistical Package for the Social Sciences (SPSS; v. 22) showing the positive learning outcomes of the participants. The rubric’s results showed that collaborative work and skills development scored higher, while contents of Social Sciences and the handling of heritage itineraries as teaching strategies were correct but lower than the other parameters analyzed. The questionnaire showed a positive perception of working together in consecutive educational levels and of the uses of digital technology for collaborative work but also indicated some difficulties regarding group organization, especially in the first weeks. The main results of the project highlight several aspects. (1) The need to apply pedagogical, technological, and educational resources to promote active and meaningful learning in future teachers. (2) The need to use virtual environments as learning and communication spaces in inter-university contexts, and (3) the importance of using local environments as scenarios for teaching Social Sciences.